Corak Moderasi Beragama (Studi Pemikiran Tokoh Muslim Moderat Salahuddin Wahid) - Idham, Ahmad (Revorma: Jurnal Pendidikan dan Pemikiran, 2022)
Salahuddin Wahid made many contributions to religion and life for the realization of harmonious people. He never attacked frontally against people who did not have the same thought. But active in providing problem-solving for a conflict. Then the researcher aims to find out his characteristics as one of the moderate figures in Indonesia so that he can be used as an example for the next generation. So, this study aims to describe Salahuddin Wahid's thoughts related to Religious moderation. This type of research is qualitative research and library research with descriptive research designs. The research data was obtained from the research process carried out by examining and exploring journals, books, and documents (both printed and electronic) as well as data sources and other information deemed relevant to research or studies. From the results of the research conducted, the researcher obtained: The attitude of moderate nationality Salahuddin Wahid emphasized more on the orientation of the national mission that is concerning the life of the Indonesian nation, the sustainability of the Indonesian nation, concerning the progress of the Indonesian nation, and concerning the life of the Indonesian people. Then the nationalist mission played a role as a guide for Partiwi by being involved in efforts to build the souls of all the people of the nation of Indonesia, and fight for the progress of the Indonesian nation. Then play a role in building the character and character of the nation, especially the leaders of the Indonesian nation, efforts to instill Indonesian and Islamic values ​​in the community through studies integrating Islam and Indonesia packed with seminars and nationality activities and involved in supporting the performance of the KPK in eradicating corruption and fighting for human rights Human.